Non-invasive imaging of cartilage in early osteoarthritis. - Palmer, A; Brown, C; McNally, E; Price, A; Tracey, I; Jezzard, P; Carr, A; Glyn-Jones, S (2013)
Treatment for osteoarthritis (OA) has traditionally focused on joint replacement for end-stage disease. An increasing number of surgical and pharmaceutical strategies for disease prevention have now been proposed. However, these require the ability to identify OA at a stage when it is potentially reversible, and detect small changes in cartilage structure and function to enable treatment efficacy to be evaluated within an acceptable timeframe. This has not been possible using conventional imaging techniques but recent advances in musculoskeletal imaging have been significant. In this review we discuss the role of different imaging modalities in the diagnosis of the earliest changes of OA. The increasing number of MRI sequences that are able to non-invasively detect biochemical changes in cartilage that precede structural damage may offer a great advance in the diagnosis and treatment of this debilitating condition.